Pemanfaatan Media Pembelajaran Digital untuk Meningkatkan Literasi Siswa pada Mata Pelajaran IPS di Sekolah Dasar - Alfina Diniyati; Nasywa Dinda Salma; Oman Farhurahman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The use of digital learning media in Social Studies subjects in elementary schools has become an important innovation in improving the quality of learning. Digital media not only enriches the learning experience, but also contributes to improving students' literacy, which includes the ability to seek, analyze and utilize information critically. However, the implementation of these media faces various challenges, such as infrastructure limitations, lack of teacher skills, content compatibility with the curriculum, and digital security issues. This research discusses digital learning media development strategies that include collaboration between educators and technology developers, intensive training for teachers, provision of adequate infrastructure, and content design tailored to the characteristics of elementary school students. Visual-based and interactive digital media is considered effective to improve students' understanding of social studies materials that are often abstract. In addition, the integration of digital learning with conventional methods provides a balanced and contextualized learning experience. By addressing the existing challenges, digital learning media can be an effective tool to strengthen students' literacy and equip them with 21st century skills. This research is expected to contribute to the development of innovative learning practices that are relevant to students' needs in the digital era.